Tyrosine kinase 2 promotes sepsis‐associated lethality by facilitating production of interleukin‐27. Issue 1 (6th March 2014) - Bosmann, Markus; Strobl, Birgit; Kichler, Nadia; Rigler, Doris; Grailer, Jamison J.; Pache, Florence; Murray, Peter J.; Müller, Mathias; Ward, Peter A.
Abstract : Tyrosine kinase 2 is required for release of IL‐27(p28) by TLR4‐activated macrophages; disruption of this pathway is protective during in vivo models of sepsis. Abstract : The aim of this study was to test the hypothesis that gene expression and release of IL‐27 may be modulated by Tyk2. Macrophages derived from the peritoneum or bone marrow of C57BL/10SnJ (WT) mice produced abundant amounts of IL‐27(p28) following TLR4 activation by LPS. In contrast, production of IL‐27(p28), but not EBI3, was reduced by ∼50% in TLR4‐activated macrophages derived from mice with genetic deficiency of Tyk2 compared with WT macrophages. Frequencies of IL‐27(p28)+F4/80+CD11b+ cells were lower in TLR4‐activated macrophages derived from Tyk2−/− mice. Mechanistically, Tyk2−/− resulted in disruption of a type I IFN‐dependent mechanism for production of IL‐27(p28), which was induced by type I IFNs, and release of IL‐27 was defective in macrophages from IFN‐β−/− and IFNAR1−/− mice. In contrast, Tyk2 was not required to mediate the effects of IL‐27 on target gene expression in CD4 + T cells. In vivo, we observed that Tyk2−/− mice have improved survival following endotoxic shock or polymicrobial sepsis induced by CLP. Plasma levels of IL‐27(p28) during endotoxic shock or polymicrobial sepsis were markedly reduced in Tyk2−/− mice compared with WT mice. Disruption of IL‐27 signaling using IL‐27RA−/− mice was protective against sepsis‐associated mortality. These data suggest that Tyk2 may mediate adverse outcomes of SIRS by promoting the production of IL‐27. In conclusion, this report identifies Tyk2 as a prerequisite factor in the molecular networks that are involved in generation of IL‐27.